ISTIRATIJIYAT TALAMIDZ AL-MARHALAH AL-TSANAWIYAH BI MA'HAD DARUSSALAM GONTOR FI TA'ALLUM MAHARAH AL-KITABAH - Putra Bagus Mochammad; Wiaam Mohammad Syairozi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2017)
This study attempted to investigate the strategies used by high school students in writing Arabic compositions, problems they confronted, and differences strategies used by the students with highest and lowest scores. The samples of this study were fifth-grade students of Darussalam Islamic Boarding School, i.e., three students with high achievements and three with low ones. Data collection techniques were used, namely thinking-aloud protocol, interview and observation. Specific processes and strategies were categorized using coding schemes adopted from Yap (1999). The result of this study revealed that the problems mostly faced by the students in writing an Arabic composition were understanding the topic and generating the idea to create a good sentence. Moreover, the study found that students were unable to select proper words, to figure out appropriate sentences and to construct simple sentences. The most commonly–used strategies were repeating words, making sentences, taking down notes and translating.